Prevalence of hearing impairment in Aligarh: a community based study - Khan, Mohammad Asif; Khalique, Najam; Khan, Zulfia; Hasan, Abrar (International Journal Of Community Medicine And Public Health, 2018)
Background: Hearing impairment is avery complex phenomenon, which has many and serious consequencesfor people and involves many factors and issues that should becarefully examined. The objective of the study were to estimate the prevalence of hearing impairment in the study population. Methods: Study design was a community based cross sectional study. Setting was on field practice areas of the urban and rural health training centers, Department of Community Medicine, Jawaharlal Nehru Medical College, Aligarh Muslim University, Aligarh, Uttar Pradesh. No. of Participants was 422 study subjects age 18 and above 18 years; Systematic random sampling and proportionate to population size method (PPS). Statistical analysis was carried out using SPSS version 13; Chi-square. Results: Overall prevalence in present study population was found to be 23.1%. The prevalence in the rural areas (24.8%) was found to be higher than that of the urban areas (20.5%). The age specific prevalence showed that the maximum prevalence was in the age group of more than 70 years (66.6%). In the rural areas the prevalence was highest in the >70 year age group(75%) while in the urban areas it was maximum in the 61-70 year age group(61.5%). The prevalence was least in the 31-40 year age group in both urban (5.4%) as well as rural areas (14.5%). The association of hearing loss with age was found to be highly significant. Conclusions:A high prevalence of hearing impairment was found in the study. Increasing prevalence of hearing impairment was observed with advancing age.